A phylogeny of Darwin's finches based on microsatellite DNA length variation - Petren, K. (1999)
Allele length variation at 16 microsatellite loci was used to estimate the phylogeny of 13 out of the 14 species of Darwin's finches. The resulting topology was similar to previous phylogenies based on morphological and allozyme variation. An unexpected result was that genetic divergence among Galápagos Island populations of the warbler finch (Certhidea olivacea) predates the radiation of all other Darwin's finches. This deep split is surprising in view of the relatively weak morphological differentiation among Certhidea populations and supports the hypothesis that the ancestor of all Darwin's finches was phenotypically similar to Certhidea. The results also resolve a biogeographical problem: the Cocos Island finch evolved after the Galápagos finch radiation was under way, supporting the hypothesis that this distant island was colonized from the Galápagos Islands. Monophyletic relationships are supported for both major groups, the ground finches (Geospiza) and the tree finches (Camarhynchus and Cactospiza), although the vegetarian finch (Platyspiza crassirostris) appears to have diverged prior to the separation of ground and tree finches. These results demonstrate the use of microsatellites for reconstructing phylogenies of closely related species and interpreting their evolutionary and biogeographic histories.